Computational fluid dynamics simulations to improve performance characteristics of a manifold having a central inlet and outlet - Ganguli, Arijit A.; Pandit, Aniruddha B. (Frontiers in Energy Research, 2022)
In the present work, performance/flow characteristics (namely effect of operating parameters like pressure on flow patterns, pressure drop and extent of flow uniformity) and transport phenomena of a manifold (header tube assembly) having inlet and outlet at center is carried out on a macroscale geometry using CFD simulations. In this study, an existing design available in published literature (with high flow nonuniformity) and an optimized design (with minimum flow non-uniformity). The optimization is performed by incorporating a perforated plate (distributor) inside the top header of the manifold. First, CFD simulations for different configurations of existing design with perforated plate have been performed for a pressure of 10 bar with steam as working fluid and an optimized configuration having minimum flow non-uniformity less than 3% is obtained. CFD simulations for both the existing design and optimized design are then performed for a pressure range (10 ≤ P ≤ 70 bars) and corresponding Reynolds number (Re) range (2.82E+05≤Re≤2.82E+06) with steam as working fluid. Extent of non-uniformity (ENU) and pressure drop for existing design (without distributor) and optimized design (with distributor) have been analyzed and compared. The optimized design gives near uniform flow (~1-4%) for all pressures and Reynolds numbers considered. An empirical correlation relating friction factor (as per Chilton Colburn analogy) and Re has been developed for both designs (with and without distributor). The predicted frictionfactors are compared with the present CFD predictions and experimental data of shell and tube heat exchanger available in published literature. A good agreement within 10-15% deviation has been observed. Based on Chilton-Colburn analogy, a correlation for Nusselt number is obtained from the friction factor correlations for both with and without distributor cases. The correlations for friction factors were found to be valid any operating conditions for a pressure drop range within 0.05 < ∆P < 1.8 bars irrespective of the design of the distributor assuming the manifold is able to withstand the pressure drops in the given range. Keywords: Manifolds, extent of non-uniformity, flow patterns, pressure drop, friction factor